ANALISIS SEMIOTIKA JOHN FISKE NILAI-NILAI DAKWAH DALAM FILM 3 : ALIF LAM MIM - Muhammad Askolani; Anton Sulaiman; Ipad Padlan Almunawar (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
This thesis discusses the John Fiske Semiotics Analysis Of The Values Of Dakwah In Film 3: Alif Lam Mim. This research is motivated by a film with a futuristic theme by telling about the world of ffriendship, brotherhood, and family drama that contains da'wah values. This study aims to describe the value of da'wah elements of faith (aqidah), elements of Islam (shari'a), elements of sincerity (morals) contained in Film 3: Alif Lam Mim. This research is a qualitative descriptive study. The research approach used in this study is a qualitative approach using John Fiske's theory of semiotic analysis. The primary data source in this study, the writer watched the movie 3: Alif Lam Mim directly and the secondary data source was obtained from literature, books, the internet, and previous studies which will be used to help the writer analyze it in more depth. While the data collection is done by watching the film, compiling a theoretical framework, dividing the film into several scenes, cutting the video (cutting), drawing conclusions from the results of the analysis. Furthermore, the results of this study indicate that the values of da'wah contained in Film 3: Alif Lam Mim: 1) The value of da'wah is an element of faith (aqidah) which is about faith in Allah SWT. 2) The value of preaching Islamic elements (shari'a) is about religious tolerance. 3) The value of preaching the element of sincerity (morality) is about commendable morals and honesty.